Consequence analysis on the critical role of transient pool formation in cold ammonia release and gas dispersion using CFD approach - Ng, Michelle Xin Yi; Yu, Kai Xiang; Ten, Joon Yoon; Tan, Khang Wei; Lam, Weng Hoong; Tan, Peng Chee; Choong, Thomas Shean Yaw; Siwayanan, Parthiban; Chen, Binghui; Kim, Kek Seong; Ban, Zhen Hong (Elsevier, 2025)
Accurate consequence modelling and risk assessment is crucial to mitigate the toxicity risks of ammonia. However, available refrigerated liquefied ammonia studies have assumed key parameters including pool size, pool shape, and lack of flashing during initial release. This work proposed a dynamic pool area estimation method for more accurate evaporation rate calculation during continuous release, rather than assume initial pool characteristics. For releases into the atmosphere, Computational Fluid Dynamics (CFD) was used for improved simulation of ammonia flashing, evaporation, and gas dispersion. The impact of wind speed, release rate, and release pressure on pool formation and ammonia gas concentration were investigated. The increase in wind speeds extended pool length, without significantly affecting size, and increased evaporation rates, but decreased hazardous zone sizes as dilution effect was stronger under wind field influence. The increasing release rates through larger hole sizes increased pool sizes, followed by higher evaporation rates and larger hazardous zones. For larger release pressures, higher release velocities formed pools further from the source, impacting initial ammonia cloud location. The results offer insights into emergency response and evacuation plan development, and the model can provide quantitative data needed for advanced digital technologies such as Artificial Intelligence (AI)-based safety systems.